Diagnostic accuracy of single-voided urine protein/ creatinine ratio for proteinuria assessment in children with nephrotic syndrome - Devie Kristiani; Pungky Ardani Kusuma; Purnomo Suryantoro (Indonesian Pediatric Society Publishing House, 2009)
Background Measurement of protein excretion is not only used for diagnostic purpose but also to monitor disease severity and prognosis in children with nephrotic syndrome (NS). The common method to measure proteinuria is 24-hour urine collection. However, 24-hour urine collection is cumbersome, time consuming, and tedious. An alternative simplified method is the measurement of protein/creatinine ratio in single-voided urine specimens. Objective The aim of this study was to determine whether urine protein/creatinine ratio is accurate to predict pathologic (> 100 mg/m2/day) and massive proteinuria (> 1 g/m2/day). Methods Seventy single voided and 24-hour urine specimens were collected from children aged 3-18 years. The relationship between urinary protein/creatinine ratio and total daily protein excretion was calculated using correlation and linear regression analysis. Diagnostic test was conducted to estimate the accuracy of protein/creatinine ratio for the diagnosis of pathologic and massive proteinuria in NS. Results Correlation coefficient between quantity of protein in 24-hour urine specimens and protein/creatinine ratio in singlevoided urine specimens was 0.96 (R2=0.93). Both sensitivity and specificity of urinary protein/creatinine ratio were 87% in diagnosing pathologic proteinuria, whereas the sensitivity and specificity of the ratio to predict massive proteinuria were 88% and 91%, respectively. Conclusion The urinary protein/creatinine ratio in single voided urine specimen has a good accuracy to predict pathologic and massive proteinuria in children with NS aged 3-18 years.